Hydroxychloroquine's Early Impact on Cone Density. (6th September 2021) - Ueda-Consolvo, Tomoko; Oiwake, Toshihiko; Abe, Shinya; Nakamura, Tomoko; Numata, Ayaka; Hayashi, Atsushi
Abstract : Purpose . To evaluate early effects of hydroxychloroquine (HCQ) on the retina using adaptive optics (AO). Methods . This was a prospective observational single-center study of 29 eyes of 29 patients who had been treated with HCQ for the first time and followed with AO for a minimum of two years. Cone counting was performed in 4 quadrants, nasal, temporal, superior, and inferior, at 0.75 mm from the foveal center. The changes of cone density on AO, visual acuity, and foveal thickness within two years of use were analyzed. The changes of mean cone density of patients whose cumulative dose was over 200 g in 2 years were also assessed. We evaluated the correlation between cone density and cumulative dose of HCQ. Results . There was no significant decrease in cone density in the first 2 years of HCQ use. VA and foveal thickness did not show obvious change, either. Among 9 patients whose cumulative dose was over 200 g in 2 years, the mean cone density showed no significant change at 6, 12, 18, and 24 months compared with baseline (P = 0.381, P = 0.380, P = 0.281, and P = 0.534, respectively). There was no correlation between cone density and cumulative dose of HCQ at two years (Spearman's correlation coefficient, r  = −0.0553, P = 0.780 ; n  = 29). Conclusion . AO showed no change in cone density in the first two years of HCQ use.